2021
DOI: 10.1002/hep4.1746
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation Between the NRF2 Pathway and Oncogenic β‐catenin During HCC Tumorigenesis

Abstract: CTNNB1 (catenin beta 1)-mutated hepatocellular carcinomas (HCCs) account for a large proportion of human HCCs. They display high levels of respiratory chain activity. As metabolism and redox balance are closely linked, tumor cells must maintain their redox status during these metabolic alterations. We investigated the redox balance of these HCCs and the feasibility of targeting this balance as an avenue for targeted therapy. We assessed the expression of the nuclear erythroid 2 p45-related factor 2 (NRF2) deto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“… 16 In support of cooperation between the Keap1–Nrf2 pathway and β-catenin signaling, a very recent article reported an enrichment of the NRF2 program in human HCCs with b-catenin (CTBBB1) mutations, largely independent of NRF2 or KEAP1 mutations. 27 The same study also showed that mice with hepatocyte-specific oncogenic β-catenin activation increased Nrf2 activation, most likely to protect β-catenin–activated hepatocytes from oxidative damage, thus favoring tumor development, and proposed cooperation between oncogenic β-catenin signaling and the NRF2 pathway in CTNNB1-mediated HCC. 27 Furthermore, an independent work showed co-activation of β-catenin and NRF2 in 9% of all human HCCs, and discovered that co-expression of mutated CTNNB1 with mutant NRF2 , but not wild-type NRF2 , led to rapid HCC development and mortality.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“… 16 In support of cooperation between the Keap1–Nrf2 pathway and β-catenin signaling, a very recent article reported an enrichment of the NRF2 program in human HCCs with b-catenin (CTBBB1) mutations, largely independent of NRF2 or KEAP1 mutations. 27 The same study also showed that mice with hepatocyte-specific oncogenic β-catenin activation increased Nrf2 activation, most likely to protect β-catenin–activated hepatocytes from oxidative damage, thus favoring tumor development, and proposed cooperation between oncogenic β-catenin signaling and the NRF2 pathway in CTNNB1-mediated HCC. 27 Furthermore, an independent work showed co-activation of β-catenin and NRF2 in 9% of all human HCCs, and discovered that co-expression of mutated CTNNB1 with mutant NRF2 , but not wild-type NRF2 , led to rapid HCC development and mortality.…”
Section: Discussionmentioning
confidence: 89%
“… 27 The same study also showed that mice with hepatocyte-specific oncogenic β-catenin activation increased Nrf2 activation, most likely to protect β-catenin–activated hepatocytes from oxidative damage, thus favoring tumor development, and proposed cooperation between oncogenic β-catenin signaling and the NRF2 pathway in CTNNB1-mediated HCC. 27 Furthermore, an independent work showed co-activation of β-catenin and NRF2 in 9% of all human HCCs, and discovered that co-expression of mutated CTNNB1 with mutant NRF2 , but not wild-type NRF2 , led to rapid HCC development and mortality. 28 Thus, it appears that the frequency of Nrf2 mutations greatly vary among HCCs occurring in different species ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations